Effect of temperature and concentration on viscosity of orange peel pectin solutions and intrinsic viscosity-molecular weight relationship - Kar, F; Arslan, N (Elsevier Sci Ltd, 1999)
The effects of temperature and concentration on the viscosity of orange peel pectin solutions were examined at five different temperatures between 20 and 60 degrees C and five concentration levels between 2.5-20 kg/m(3). The effects of temperature was described by an Arrhenius-type equation. The activation energy for viscous how was in the range 19.53-27.16 kJ/mol, depending on the concentration. The effect of concentration was described by two types of equation, power-law and exponential. Equations were derived which describes the combined effects of temperature and concentration on the viscosity for two different models in the range of temperatures and concentrations studied. Orange peel pectin was extracted by using HCl (pH 2.5, 90 degrees C, 90 min) ammonium oxalate (0.25%, pH 3.5, 75 degrees C, 90 min) and EDTA (0.5%, 90 degrees C, 90 min) extraction procedures. The best result was obtained with ammonium oxalate extraction in which the pectin content of the final product was 30.12%, although the efficiency among the procedures varied. The average molecular weight was measured by light scattering technique. Magnitudes of intrinsic viscosity and molecular weight of pectins obtained by extraction with HCl, ammonium oxalate and EDTA were 0.262, 0.281, 0.309 m(3)/kg and 84 500, 91 400, 102 800 kg/kgmol, respectively. The molecular weight dependence of the intrinsic viscosity of the orange peel pectin solutions was expressed by Mark-Houwink-Sakurada equation. The data were fined to equation as eta(i) = 2.34 X 10(-5) (M-w,M-ave)(0.8224) which helps to evaluate the average molecular weight of pectin solutions from orange peel with a knowledge of their intrinsic viscosity. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: orange peel pectin solutions; jam manufacturing; viscosity; temperature and concentration dependence; molecular weight